MENINGKATKAN PERKEMBANGAN KOGNITIF ANAK MELALUI MEDIA KARTU ANGKA DARI KARDUS BEKAS DI PAUD CERIA DESA PAGAR AGUNG KECAMATAN SELUMA BARAT KABUPATEN SELUMA - Gusniarti Gusniarti; Dwi Nomi Pura; Mimpira Haryono (Early Childhood Research and Practice, 2020)
The purpose of this study was to determine the improvement of children's cognitive development through the media of cardboard number cards in PAUD CERIA, Pagar Agung Village, Seluma Barat District, Seluma Regency, to find out whether the use of used cardboard number card media can improve children's cognitive development in PAUD CERIA, Pagar Agung Village. Seluma Barat District, Seluma Regency. Classroom Action Research (CAR), which focuses on classroom situations, or commonly known as classroom action research, the procedure used is in the form of a cycle. The main subjects in this study were children of PAUD CERIA Desa Pagar Agung Kec. West Seluma Kab. Seluma group B numbered 16 people. Data collection techniques using observation and documentation methods. Data analysis was carried out in a descriptive qualitative-quantitative manner with the emphasis being used to determine the improvement in the process expressed in a predicate, while quantitative data analysis was used to determine the increase in yield using a percentage. The research concludes that the cognitive development of children through the media of card numbers from used cardboard in PAUD Ceria Pagar Agung Village, Seluma Barat District, Seluma Regency is well developed.